1999
DOI: 10.1002/j.1550-8528.1999.tb00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Overeating in America: Association between Restaurant Food Consumption and Body Fatness in Healthy Adult Men and Women Ages 19 to 80

Abstract: McCRORY, MEGAN A., PAUL J. FUSS, NICHOLAS P. HAYS, ANGELA G. VINKEN, ANDREW S . GREENBERG, AND SUSAN B. ROBERTS. Overeating in America: association between restaurant food consumption and body fatness in healthy adult men and women ages 19 to 80. Obes Res. 1999;7:564-57 1. Purpose: To examine the association between the frequency of consuming restaurant food and body fatness in adults. Research Methods and Procedures: Usual free-living dietary intake and the frequency of consuming food from seven different res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(188 citation statements)
references
References 23 publications
15
167
2
3
Order By: Relevance
“…Moreover the fat content was often high (36?6 % of the items overall contained $20 g fat/portion; Table 2). This is in agreement with data in the literature (6,7,13) reporting that foods from restaurants, canteens, cafeterias and similar establishments are generally high in energy and fat when compared with home-prepared foods. In addition, various studies have shown that OHE is associated with higher energy intakes due to the meals' higher energy density (2,6,7,(15)(16)(17) or larger portion size (30)(31)(32)(33) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover the fat content was often high (36?6 % of the items overall contained $20 g fat/portion; Table 2). This is in agreement with data in the literature (6,7,13) reporting that foods from restaurants, canteens, cafeterias and similar establishments are generally high in energy and fat when compared with home-prepared foods. In addition, various studies have shown that OHE is associated with higher energy intakes due to the meals' higher energy density (2,6,7,(15)(16)(17) or larger portion size (30)(31)(32)(33) .…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence rates of overweight and obesity in our sample were well below the Italian national data (34) reporting in 2005 that 42?5 % of males and 26?6 % of females were overweight and 10?5 % and 9?1 %, respectively, were obese. We cannot say if OHE is associated with the prevalence rates of overweight and obesity in our sample, as some studies have shown (6,(8)(9)(10)16,21,22,(31)(32)(33) , since in the interview we did not ask customers how long they had been eating in the cafeteria and if their weight had increased during that period of time. This is a limitation of our study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, our finding that, among carbohydrates, OH eating contributed more to sugar intake was expected; in a previous publication using the same data and reporting OH food and beverage intake (Orfanos et al, 2007), it was found that sweets (including sugar, confectionery and cakes), soft drinks and other nonalcoholic beverages were items selectively consumed out of home. Our result that OH eating contributed less to total fibre intake (especially in the southern countries) is generally consistent with the results of American and Australian studies (Haines et al, 1992;McCrory et al, 1999;French et al, 2000;Burns et al, 2002;Guthrie et al, 2002), as well as of studies based on European data (Kearney et al, 2001;O'Dwyer et al, 2005). As in our study, previous publications reported that OH eating contributed less to total micronutrient intakes than in-home eating (Kearney et al, 2001;Bowman and Vinyard, 2004;O'Dwyer et al, 2005).…”
Section: S253supporting
confidence: 93%
“…As people spend more time working in formal labor markets, they spend less time on food preparation. Nutritional quality of meals eaten away from home in U.S. is generally poorer than meals prepared at home (McCrory et al 1999;French et al 2000;Diliberti et al 2004). Brazil has adopted dietary guidelines that emphasize home cooking because of the negative relationship between food cooked outside the home and diet quality/disease risk (Brazil Ministry of Health 2014).…”
Section: Conveniencementioning
confidence: 99%